Rapid and Sensitive Detection of Aflatoxin B1, B2, G1 and G2 in Vegetable Oils Using Bare Fe3O4 as Magnetic Sorbents Coupled with High-Performance Liquid Chromatography with Fluorescence Detection. (17th June 2020) - Zhang, Hui-Xian; Zhang, Ping; Fu, Xiao-Fang; Zhou, You-Xiang; Peng, Xi-Tian
Abstract: This paper reports a simple, sensitive and reliable method for the simultaneous detection of aflatoxin B1, B2, G1 and G2 in vegetable oils. Aflatoxins were extracted by magnetic solid phase extraction followed by high-performance liquid chromatography, then postcolumn photochemical derivatization and finally detected by fluorescence detector. Vegetable oil samples were first diluted with hexane and then commercial bare Fe3 O4 nanoparticles were directly employed as sorbents to extract aflatoxins from complex vegetable oil samples, which significantly simplified the procedure of sample preparation and largely improved the sample analysis throughput. The effects of various parameters such as the amount of sorbent, loading, washing and eluting conditions were carefully optimized to improve the extraction efficiencies of aflatoxins. Under the optimal conditions, the limits of detection of four aflatoxins ranged from 0.01 μg/kg to 0.16 μg/kg, and squared regression coefficients (R 2 ) >0.9990 were obtained within the linear range of 0.1–20 μg/kg (except for aflatoxin G2 with 0.5–20 μg/kg). Furthermore, the recoveries spiked at four concentration levels in a blank vegetable oil sample were from 82.6 to 106.2%, with inter- and intraday relative standard deviations <9.8%, indicating good accuracy and precision of the proposed method.